Shakespeare 24/25: to the museum with the Bard (Altre Modernità, 2024)
The 2022 ICOM (International Council of Museums) reunion gave a new definition of the word “museum”. Based on this ground, what can be the function of a Shakespeare museum today? Shakespeare is the quintessence of the English author. It was not easy to “export” him and open a vast library and a museum devoted to him in the United States (the Folger Shakespeare Library) and it is still not easy to open a new Museum of Shakespeare in London (opening delayed to 2025). In this case, based also on recent political events (ex. Brexit), the museum becomes a means for claiming an identity that is intended to be preserved. This essay analyzes what the function of a Shakespearean museum can be today, starting with an overview of the “cultures of commemoration” and using the Folger Shakespeare Library in Washington and the future Museum of Shakespeare in London as examples preceded by an historical introduction. Besides the theme, both institutions are united by the fact that they are undergoing restructuring –the former– or construction –the latter. After delving into these themes, the essay concludes with further reflection on the relationship between “cultures of commemoration” and the “museum” as an institution.
Keywords: Shakespeare; Museum; Identity; “Cultures of commemoration”; Folger Shakespeare Library; Museum of Shakespeare